2018
DOI: 10.1136/jmedgenet-2018-105362
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of genetic knowledge on intentions and attitudes of the community towards expanded preconception carrier screening

Abstract: Knowledge is instrumental in influencing participation. Having good genetic knowledge may not be enough to understand core concepts of PCS and may impact informed decision-making. This study recommends that continuous education of health professionals and thus the community, in PCS is crucial to reduce misconceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 39 publications
4
50
1
Order By: Relevance
“…As hypothesized, relatives of MPS III patients scored significantly better on the genetic knowledge test compared with the participants from the general population and might explain the more positive attitudes toward ECS of relatives, as was previously described by Ong et al [ 13 ].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…As hypothesized, relatives of MPS III patients scored significantly better on the genetic knowledge test compared with the participants from the general population and might explain the more positive attitudes toward ECS of relatives, as was previously described by Ong et al [ 13 ].…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies in the USA, Sweden and the Netherlands have investigated the opinions of the general population toward universal preconception ECS and reported that between 30% and 34% of the respondents would consider to use preconception ECS [ 10 12 ]. The study by Ong et al, conducted in Australia, showed that genetic knowledge, i.e., baseline knowledge on genetics, is instrumental in influencing ECS participation [ 13 ]. Several other studies also underpinned that genetic knowledge and experiential knowledge, i.e., the objective and subjective knowledge gained from experience with the disease, influence and shape decision making on participating in genetic testing and understanding of carrier test results [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Furthermore, we found prior knowledge, and high perceived benefits for offspring were significantly associated with the increased likelihood of intention for ECS, which agree with previous reports on the importance of awareness and knowledge in decision-making for carrier screening. [31][32][33] This finding is also theoretically based by Health Belief Model, which has confirmed that perceived benefits can influence individual's intention, attitudes and eventual behavior. 34 Taken together, the above findings suggest that propaganda work of ECS should be carried out as early as possible, ideally before marriage or pregnancy, to create a favorable social environment.…”
Section: Discussionsupporting
confidence: 70%
“…GPs are the health professionals most likely to see individuals and couples prior to pregnancy. As couples planning, or in the early stages of, pregnancy are exposed to advertising from companies offering carrier screening and/or are informed about screening by families and friends, 18 GPs will increasingly be asked about what screening is available and how it can be accessed. As many GPs are not currently familiar with carrier screening, it is important for them to upskill to be comfortable offering this testing.…”
Section: Key Pointsmentioning
confidence: 99%